IDENTIFIKASI KEBUDAYAAN SUKU KAILI YANG MEMBENTUK CITRA KOTA PALU DI KECAMATAN TAWAELI - Deltri Dikwardi Eisenring; Takwim, Supriadi; Ryan, Muhammad; Fransisko, Aang (Jurusan Teknik Perencanaan Wilayah dan Kota, Fakultas Sains dan Teknologi, Universitas Islam Negeri Alauddin Makassar, 2025)
The Kaili tribe plays a significant role in shaping the image of Palu City through various cultural aspects such as art, customs, language, and traditions. The culture of the Kaili people is reflected in the city’s architecture, spatial arrangement, and daily activities of its residents. Based on these conditions, the researcher is interested in identifying the cultural elements of the Kaili tribe within the spatial structure of Palu City by observing their activity patterns and gathering places that contribute to the formation of the city’s image. This study aims to identify the role of Kaili culture in shaping the image of Palu City, focusing on the Tawaeli District, specifically the Panau and Baiya sub-districts. A qualitative descriptive method was employed, utilizing an ethnographic approach to identify cultural symbols and their relationship to the image of Palu City, which were then mapped through the behavioral mapping method. The results of the study show that the path elements, such as routes once used for traditional rituals, though many of these rituals are no longer practiced, still function as connections between key points in the community’s social life. The edge elements, such as the Tawaeli River and the coastal boundary of Palu Bay, serve as physical separators regulating activities between the land and sea areas. The district elements indicate a spatial division based on social status and dominant economic activities within each area. The node elements, such as traditional markets and monuments, serve as centers of economic and social activity, with monuments representing the identity of the Kaili people. Furthermore, landmark elements, such as the Tawaeli King’s Cemetery Park and traditional houses, play a vital role as sources of pride and the preservation of cultural values.